Electroencephalogram based Emotion Recognition with Graph Convolutional Network Model - Islam, Md. Tahmidul; Kabir, Abrar; Chowdhury, Imtiaz Ahmed; Afrin, Sadiya; Nahin, Rakibul Alam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.